Dismissal, distrust, and dismay: A phenomenological exploration of young women's diagnostic experiences with endometriosis and subsequent support. (September 2022) - Wren, Georgina; Mercer, Jenny
Endometriosis is associated with extensive physical and emotional difficulties, yet there is little research investigating the impact of the diagnostic journey particularly for younger women. Using semi structured on-line interviews and an interpretative phenomenological analysis, this study explored nine young women's experiences of the diagnostic process and the significance of support during this period. Three main themes emerged: 'the pursuit of a diagnosis', 'adjusting to a new normality' and 'the importance of effective support'. These experiences revealed clinical shortcomings and potential improvements to current guidelines and practices to facilitate a more emboldening process for patients.